"On–off–on" pyrene‐based fluorescent chemosensor for the selective recognition of Cu2+ and S2− ions and its utilization in live cell imaging. (11th January 2020) - Rajasekaran, Dhivya; Venkatachalam, Kavitha; Periasamy, Viswanathamurthi
Abstract : A new "on–off–on" fluorescence chemosensor (DPD) was designed, synthesized, and characterized based on pyrene and benzothiozole hydrazide. The probe DPD shows high affinity towards Cu 2+ ions and the DPD‐Cu 2+ ensemble shows high sensitivity towards S 2− ions through the displacement method in the presence of other interfering ions. The detection limits of DPD for Cu 2+ and S 2− ions were found to be 0.73 and 0.87 nM, respectively. Furthermore, the receptor was effectively applied to recognize Cu 2+ and S 2− ions in real samples and live A549 cells through imaging studies. Abstract : A new pyrene‐based fluorescence sensor (DPD) capable of detecting Cu 2+ and S 2− ions was synthesized and characterized. The sensor was used to identify these ions in real water samples and live cells.